Conical beam windmill-shaped array antenna design based on quarter-mode substrate integrated waveguide - Cheng, Jin (2014)
This paper presents a compact conical beam antenna based on quarter-mode substrate integrated waveguide (QMSIW). The antenna array is consisted of six isosceles right-angled triangle metallic patch printed on the upper side of the substrate in a windmill-shape and diagonal periodic metallic via holes drilled along the hypotenuse of the triangle patch. The planer structure exhibits conical beam radiation. The typical radiation is obtained at 5.2 GHz with conical beam radiation pattern. The measured gain is about 5.36 dBi and the radiation efficiency is around 50%.